Simultaneously Election Impact On The Presidential System In Indonesia - Moh Priyo Manfaat (Jurnal Daulat Hukum, 2019)
Indonesia for the first time do Election simultaneously. This election is different from the previous elections. Although Election simultaneously in contrast to previous elections, the Election simultaneously turns both have relevance to the presidential government system in Indonesia. The relevance can be seen from the historical aspect of the previous elections. That is because the Election simultaneously substantially the same as the previous election. The difference lies only in the electoral mechanism simultaneously. However, simultaneous Elections must also be assessed whether the impact of the strengthening of the presidential system of government in Indonesia. This paper reviews the relevance of electoral simultaneously with the presidential system of government in Indonesia.Keywords: Impact; Simultaneous Elections: Presidential